Field study of low-energy long-distance wireless communication for IoT application in remote areas - Kwai, Yang Sak; Ahmad Najmuddin, Ibrahim (Penerbit UMP, 2020)
Long Range (LoRa) is a wireless radio frequency technology under the Low Power Wide Area Network (LPWAN). LoRa is able to communicate long range and low energy consumption. The communication range has become an essential element in the wireless radio frequency technology in the Internet of Things (IoT). The presence of LoRa is able IoT application performs in long communication distances with high noise sensitivity ability. People can operate, monitor, and do a variety of tasks from a remote distance. Therefore, this research aims to evaluate the performance of the LoRa connection between radio transceivers in remote locations. The different environment and structural elements affect the LoRa performance. This thesis will be supported by the experiment that LoRa communication in different environments and tests. This experiment tests in line of sight (LOS) and non-line of sight (NLOS). Two sets of LoRa parameters, including Spreading Factor (SF), Bandwidth, and coding rate, are tested in different environments. The experiment tests the LoRa performance in various aspects: received signal strength indicator (RSSI) and packet received ratio (PPR) at different coverage ranges. In addition, the LoRa performance is evaluated in university, residential areas and vegetation areas under similar temperature, weather, and time. The LoRa coverage distance in the vegetation area and university area is reached 900 meters in the LOS test. Still, the vegetation area's signal is more stable and able to receive weaker RSSI signals. The LoRa coverage distance in the NLOS test is shorter compared to the LOS test. NLOS test has only one-third of the LOS LoRa communication distance. It is due to the signal penetration on structural elements such as buildings and woods cause the signal power loss and only transmitting a shorter distance. The LoRa parameter with SF9, 31.25kHz bandwidth and 4/8 coding rate has a better coverage range and stable connection.